HUBUNGAN SELF ESTEEM DENGAN PERILAKU SOSIAL ANAK USIA 4-5 TAHUN DI TK AISYIAH PERAWANG KABUPATEN SIAK - Essy Putri Fatimah; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the relationship between self esteem and social behavior of 4-5 year olds in TK Aisyiah Perawang, Siak Regency. The sampling tool uses saturated sample techniques, the subject set in this study is 40 children aged 4-5 years. Data collection in this study is primary data, using observation sheets. Data analysis techniques using the t-test using SPSS 17.0 program. The research hypothesis is that there is a relationship between self esteem and social behavior of 4-5 year olds in TK Aisyiah Perawang, Siak Regency. Based on data analysis, it is known that t count = 6.450> t table = 2.021 with Sig. (2-tailed) = 0,000. Because Sig <0.05, it can be concluded that there is a relationship between self esteem and social behavior. It can be interpreted that there is a relationship between self esteem and social behavior of children aged 4-5 years in TK Aisyiah Perawang, Siak Regency, at 52.3%.Key words: social behavior, self esteem